Potensi Antidiabetik Tepung Terung Ungu (Solanum Melongena L.) pada Tikus Hiperglikemia - Hasmar Fajriana (Politeknik Kesehatan Kemenkes Mamuju, 2022)
Diabetes Mellitus (DM) is a group of metabolic diseases characterized and identified with hyperglycemia due to impaired insulin secretion, insulin action, or both, and the presence of impaired metabolism of carbohydrates, fats, and proteins. IDF data shows the prevalence is increasing from year to year, namely 9.3% (2020) and 10.5% (2021). Treatment of DM was needed a combination of pharmacological and non-pharmacological treatment by utilizing local foods in the diet. Purple eggplant (Solanum melongena L.) is one of the potential plants in Indonesia that is very rich in antioxidants and believed to decrease fasting blood glucose (FBG) levels. The study aimed to determine the effect of purple eggplant flour (TTU) on the weight and fasting blood glucose levels of hyperglycemia rats. This true experimental study design used a pre-post test with a control group design. Thirty-six male Sprague Dawley rats were divided randomly into five groups: KN group (7 rats), KD (8 rats), P1 (7 rats), P2 (7 rats), and P3 (7 rats). The rats used were 10-12 weeks, weighing 207.25Â±26.76 grams. The hyperglycemia rat model was made by induced NA (230 mg/kg body weight)-STZ (65 mg/kg body weight) intraperitoneally. Intervention in the form of TTU modified feed (standard feed is substituted with TTU according to the dose) was given for 28 days with dose variations of 2.36 grams, 4.71 grams, and 7.07 grams. Body weight and FBG level were measured before and after the intervention. Data were analyzed statistically using One Way Anova test, Bonferroni test, and uji paired t-test. The body weight of DM rats was significantly lower, and FBG levels were significantly higher than normal rats (KN). Orally administration of TTU for 28 days significantly increased body weight (6.59%-19.54%) and reduced levels of FBG (33.04-54.61%). The changes in FBG levels were in line with the increasing doses of intervention. Purple eggplant flour was able to maintain body weight and reduce the levels of FGB hyperglycemia in rats induced by NA-STZ.